Latin American Students and Language Learning in Catalonia: What does the Linguistic Interdependence Hypothesis show us? - Huguet, Angel (The Spanish journal of psychology, 2014)
The massive arrival in Spain of students of immigrant origin has visibly altered the traditional configuration of schools, where ethnic, cultural and linguistic diversity is becoming increasingly manifest. This situation is worth being mentioned insofar as it affects all the different autonomous communities in the country, even more clearly Catalonia, where the educational system is organized under the parameters of bilingual education. One of the theoretical constructs supporting this educational model is the Linguistic Interdependence Hypothesis, developed by Jim Cummins at the beginning of the 1980s. According to the author, whenever the instruction in a given language (Lx) takes place under certain conditions, competence acquired in this language can be transferred onto another (Ly). Bearing this theoretical construct in mind, our study focuses on a sample of 237 Spanish-speaking subjects (123 native and 114 immigrant students) who completed a series of parallel tests evaluating their skills in Catalan and Spanish. Drawing on the data analyzed we can conclude that the Hypothesis accounts for the results in both native and immigrant students with the same L1.